The effect of corporate governance elements on employee performance: evident form ghanaian banking industry - Osei, Francis; Yankah, Rose; Agyapong, Julia; Owusu-Mensah, Samuel (Technium Business and Management, 2022)
This study observes the impact of elements of corporate governance on employee performance: evident form Ghanaian banking industry. The study was conducted on total of 200 public sector employees in Ghana, out of which 150 responses were received representing 75% response rate. Purposive and convenience sampling techniques were adapted. The study employed an explanatory research design. The study used PLS-SEM technique was used to determine the relationships among the variables. The study also found that there is significant relationship between employees’ performance and leadership style. Furthermore, it was discovered that internal systems and control had a major impact on employee performance. Furthermore, no substantial link was seen between employee performance and corporate culture. There was, however, a strong link between organizational structure and employee performance. Corporate governance processes have been found to have a direct influence on employee performance. As a result, this research adds a new dimension to corporate governance procedures and employee performance, providing a basis for new policy direction in businesses. As a result, the study comes to the conclusion that corporate governance has a favorable impact on employee performance. This suggests that the board of directors and owners of an organization must enhance their interest in the organizational culture, structure, leadership style, and systems of control displayed in their organization to ensure improved employee performance for the firm as a whole.